2015
DOI: 10.1038/srep17596
|View full text |Cite
|
Sign up to set email alerts
|

Tunable Magnetization Dynamics in Interfacially Modified Ni81Fe19/Pt Bilayer Thin Film Microstructures

Abstract: Interface modification for control of ultrafast magnetic properties using low-dose focused ion beam irradiation is demonstrated for bilayers of two technologically important materials: Ni81Fe19 and Pt. Magnetization dynamics were studied using an all-optical time-resolved magneto-optical Kerr microscopy method. Magnetization relaxation, precession, damping and the spatial coherence of magnetization dynamics were studied. Magnetization precession was fitted with a single-mode damped sinusoid to extract the Gilb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 41 publications
1
33
0
Order By: Relevance
“…2(a) and 2(c) with three characteristic regions can be understood by considering several intrinsic and extrinsic effects occurring at the interface of the FM and NM layers. It is known that d-d hybridization, spin-pumping, and two-magnon scattering are the effective factors for damping enhancement in FM/NM thin films [3,4,11,13,17,21,23]. The experimental results are in agreement with a recent theoretical study [3] where damping increases with increasing Pt capping layer thickness up to a broad peak followed by a decrease to constant value with further increases in thickness.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…2(a) and 2(c) with three characteristic regions can be understood by considering several intrinsic and extrinsic effects occurring at the interface of the FM and NM layers. It is known that d-d hybridization, spin-pumping, and two-magnon scattering are the effective factors for damping enhancement in FM/NM thin films [3,4,11,13,17,21,23]. The experimental results are in agreement with a recent theoretical study [3] where damping increases with increasing Pt capping layer thickness up to a broad peak followed by a decrease to constant value with further increases in thickness.…”
Section: Discussionsupporting
confidence: 87%
“…Understanding and controlling damping in thin film systems therefore continues to drive research in this field. It has been demonstrated that damping can be enhanced in both bulk ferromagnetic (FM) [1][2][3][4] and multilayered systems [5][6][7][8] and many studies have addressed the fundamental origin of damping both experimentally and theoretically [1,3,[9][10][11][12][13][14][15]. Both Co and Ni 81 Fe 19 have attracted a lot of attention due to their common application in magnetic devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The discrepancies between the previous studies may be associated with the details of the multilayered structure. In particular, the nature of the interface structure in such systems is known to be important for spin-pumping 17,18 and in the ultra-thin film regime the presence of a continuous intermediate layer needs to be established when studying such interlayer effects 19 . Spin pumping and d − d hybridization across a FM/NM interface both lead to additional magnetic energy loss and increased precessional damping.…”
mentioning
confidence: 99%
“…However, the comparison of our results with the experimental data is hindered not only by the different interface/surface orientation in the theoretical structures and the experimental multilayers but also by the fact that the Co/NM interfaces in the experimental (111) fcc Co/Pd and Co/Pt layered systems exhibit significant roughness and strong intermixing [65,71]. Such structure imperfections can lead to enhancement of α as observed in L1 0 FePt films [27] as well as an additional magnetic damping due the two-magnon scattering [40,41,72], which may become particularly significant if the external magnetic field is applied parallel or at a small angle to the film surface. The resulting extra damping terms can account for the difference between the effective Gilbert damping constant measured in experiment and the present theoretical results without resorting to the use of very small scattering rates.…”
Section: -5mentioning
confidence: 95%